1985
DOI: 10.1002/bjs.1800720415
|View full text |Cite
|
Sign up to set email alerts
|

Early gastric carcinoma in Japanese patients under 30 years of age

Abstract: The clinicopathological characteristics of early gastric carcinoma (EGC) in 23 Japanese under 30 years of age were reviewed and the findings compared with data on 53 patients over age 70. In the young patients, there was a female preponderance, a macroscopic solitary lesion and the cancer was of the poorly differentiated type without intestinal metaplasia in the surrounding mucosa. In the old patients, there was a male preponderance; about half the number of patients had macroscopically elevated lesions and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
36
0
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 16 publications
16
36
0
4
Order By: Relevance
“…With regard to glandular atrophy and intestinal metaplasia of the background mucosa, our young patients were mostly infected by H. pylori, however, they had less degree of corporal glandular atrophy and less frequent intestinal metaplasia around the intramucosal gastric cancer than elderly patients did. This result is consistent with that of the previous report by Mori et al 2 On the other hand, Koshida et al 18 reported that there was significantly higher prevalence of H. pylori infection, glandular atrophy and intestinal metaplasia in cases with gastric cancer than in cases without gastric cancer in young patients. This result is not consistent with the above ones including ours, however, Koshida et al 18 treated with patients younger than 40 years old (total of 40 patients, including only nine patients under 30 years of age).…”
Section: Intramucosal Gastric Cancer In the Youngsupporting
confidence: 92%
See 3 more Smart Citations
“…With regard to glandular atrophy and intestinal metaplasia of the background mucosa, our young patients were mostly infected by H. pylori, however, they had less degree of corporal glandular atrophy and less frequent intestinal metaplasia around the intramucosal gastric cancer than elderly patients did. This result is consistent with that of the previous report by Mori et al 2 On the other hand, Koshida et al 18 reported that there was significantly higher prevalence of H. pylori infection, glandular atrophy and intestinal metaplasia in cases with gastric cancer than in cases without gastric cancer in young patients. This result is not consistent with the above ones including ours, however, Koshida et al 18 treated with patients younger than 40 years old (total of 40 patients, including only nine patients under 30 years of age).…”
Section: Intramucosal Gastric Cancer In the Youngsupporting
confidence: 92%
“…In several studies, the clinicopathological features of gastric cancer in the young were somewhat different from ours. 1,2,[9][10][11][12][13][14]3,[15][16][17][18][19] With regard to histological type, poorly differentiated adenocarcinoma tends to be more frequent in young adults, [12][13][14]3 however, there is no difference in sex distribution between the young and elderly patients. 9,10,13,14 The discrepancy (b) Fifty-seven-year-old male subject (same case as a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early gastric cancer (EGC) now accounts for over 50% of all gastric malignancies in most Japanese hospitals (Hioki et al, 1990;Maehara et al, 1992). As these incidences have increased, the clinicopathological features of EGCs have been gradually elucidated by various authors (Mori et al, 1985;Ohta et al, 1987;Moreaux et al, 1993). The accumulation of patients with EGCs has allowed the investigation of atypical EGCs (Noguchi et al, 1985;Ichiyoshi et al, 1990; Kitamura et al, 1996a); early gastric cancers mimicking advanced gastric cancers (EGC mimicking AGC) is one such variant.…”
mentioning
confidence: 99%